Crustal velocity structure in the South Yellow Sea revealed by the joint tomographic inversion of reflected and refracted seismic waves - Ma, Fei; Hou, Fanghui; Li, Tongyu; Wu, Zhiqiang; Zhang, Jianzhong (Frontiers in Earth Science, 2023)
The crustal velocity structure in the South Yellow Sea (SYS) Basin is crucial for understanding the basin’s geological structure and evolution. OBS (ocean-bottom station) data from the OBS2013 line have been used to determine the crustal velocity structure in the SYS. The velocity model of the upper crust in the northern SYS was determined using first-arrival traveltime tomography. The model showed a higher resolution shallow crustal velocity structure but a lower resolution middle-lower crustal velocity structure. The crustal velocity structure, together with the Moho discontinuity in the SYS Basin, was also constructed using a human–computer interactive traveltime simulation, and the result was highly dependent on the prior knowledge of the operator. In this study, we reconstructed a crustal velocity model in the SYS Basin using a joint tomographic inversion of the traveltime and its gradient data of the reflected and refracted waves picked from the OBS data. The resolution of the inverted velocity structure from shallow-to-deep crust was improved. The results revealed that the massive high-velocity body below the Haiyang Sag of the Jiaolai Basin extends to the Qianliyan Uplift in the SYS; the low-velocity Cretaceous strata directly cover the pre-Sinitic metamorphic rock basement of the Sulu orogenic belt; and the thick Meso-Paleozoic marine strata are retained beneath the Meso–Cenozoic continental strata in the northern depression. The Moho depth in the SYS Basin ranges from 28 to 32 km.